Students’ Self-Confidence and Mathematical Creativity through Visual Media-Assisted Problem-Based Learning: A Descriptive Study - Raudhatunnur, Raudhatunnur; Dewanti, Sintha Sih (FKIP Universitas Lampung, 2025)
Self-confidence and mathematical creativity are two essential competencies in 21st-century learning, yet they are often insufficiently addressed through conventional instructional models. This study aims to describe and analyze students’ self-confidence and mathematical creativity after participating in a Problem-Based Learning approach supported by visual media. This study employed a quantitative approach using a quasi-experimental posttest-only control group design. The sample consisted of 50 fourth-grade students divided into an experimental and a control group. The research instruments included a self-confidence questionnaire and a mathematical creativity test, both of which had been validated and found reliable. Data were analyzed using an independent samples t-test after confirming the assumptions of normality and homogeneity. The results showed that the experimental group obtained significantly higher self-confidence scores (M = 67.68) than the control group (M = 61.28), with p < .001. Similarly, the mathematical creativity scores of the experimental group (M = 85.60) were higher than those of the control group (M = 75.80), with a p-value of .003. These results suggest a positive association between participation in visual media-based PBL and students’ self-confidence and mathematical creativity. The findings indicate that the visual media-based PBL approach may support the development of both affective and cognitive competencies in elementary students. This study provides practical insights for educators in implementing contextual learning strategies that align with the demands of 21st-century education. Keywords: problem-based learning, visual media, self-confidence, mathematical creativity.